Protein Intake Adequacy and Nutritional Status among Early Adolescents in Ile-Ife, Osun State, Nigeria: A Cross-sectional Descriptive Survey - Tobiloba Philip Olatokun; Olamide Faith Abiodun; Oluwatobi Michael Onasanya; Abdulquadri Adeoniye Adebayo; Adekunle Baki Abdulkareem; Yuliia Oliinyk; Swetha Manoj; Adediran Fahidah; Mobolaji Deborah Olabode; Oge Sunday Onwe; Lawal Habiba; Faith Ukagwu; et al. (Asian Journal of Medicine and Health, 2026)
Background: Adolescence is a vital period of growth and development that requires adequate nutrition to support both physical and mental maturation. Inadequate protein intake and poor nutritional status remain public health concerns in developing countries. Aim: This study examined whether early adolescents in the Ife Central Local Government Area (LGA) of Osun State, Nigeria, met their protein requirements, assessed their nutritional status, and identified the factors influencing these outcomes. Methods: A descriptive cross-sectional study was conducted among 365 adolescents aged 10–14 years, selected using a simple random sampling technique. Data were collected using a semi-structured, self-administered questionnaire covering sociodemographic characteristics, dietary patterns, and a 24-hour dietary recall. Anthropometric data were assessed using WHO AnthroPlus software to evaluate nutritional indices. Protein adequacy was determined based on the estimated average requirement (EAR) and recommended dietary allowance (RDA). Data were analysed using IBM SPSS Statistics version 25, with the significance level set at p < 0.05. Results: Most participants (94.0%) had adequate protein intake. The prevalence of underweight, overweight, obesity, and stunting was 6.6%, 8.8%, 2.5%, and 8.2%, respectively, indicating the coexistence of undernutrition and overnutrition. There was no significant association between protein adequacy and BMI-for-age (p = 0.060). Socioeconomic status significantly affected nutritional outcomes, with adolescents from higher social classes displaying better nutritional indices. Conclusion: The findings indicate that early adolescents in Ife Central LGA generally have satisfactory protein intake, although some forms of malnutrition remain. Socioeconomic factors had a greater influence on nutritional status than protein intake alone. This study highlights the importance of focusing on early adolescents—an often-overlooked group in national nutrition research—and provides context-specific data for policy development and intervention efforts. Emphasising balanced diets, increasing food diversity, and reducing socioeconomic inequalities are important steps towards maintaining adolescent nutritional health and progressing towards Sustainable Development Goal 2 (Zero Hunger).